Heat, molecular vibrations, and adiabatic driving in non‐equilibrium transport through interacting quantum dots. Issue 11 (14th August 2013) - Haupt, F.; Leijnse, M.; Calvo, H. L.; Classen, L.; Splettstoesser, J.; Wegewijs, M. R.; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
Abstract In this article we review aspects of charge and heat transport in interacting quantum dots and molecular junctions under stationary and time‐dependent non‐equilibrium conditions due to finite electrical and thermal bias. In particular, we discuss how a discrete level spectrum can be beneficial for thermoelectric applications, and investigate the detrimental effects of molecular vibrations on the efficiency of a molecular quantum dot as an energy converter. In addition, we consider the effects of a slow time‐dependent modulation of applied voltages on the transport properties of a quantum dot and show how this can be used as a spectroscopic tool complementary to standard dc‐measurements. Finally, we combine time‐dependent driving with thermoelectrics in a double‐quantum dot system –a nanoscale analog of a cyclic heat engine –and discuss its operation and the main limitations to its performance.